A structured approach to remediation site assessment: lessons from 15 years of fish spawning habitat creation in the St. Clair‐Detroit River System. Issue 4 (19th April 2021) - Fischer, Jason L.; Roseman, Edward F.; Mayer, Christine; Wills, Todd; Vaccaro, Lynn; Read, Jennifer; Manny, Bruce; Kennedy, Greg; Ellison, Rose; Drouin, Richard; DeBruyne, Robin L.; Cotel, Aline; et al.
Abstract : Ideally, restoration re‐establishes natural processes in degraded habitats (e.g. flow and sediment regimes). However, in altered systems where process‐based restoration is not feasible, habitat construction is another approach to mitigate degradation. Because habitat construction does not directly focus on restoring processes that build and maintain desired habitats, projects must be developed and placed within the contemporary regulatory, ecological, and hydrogeomorphic context of a system, to maximize effectiveness. Here, we develop a framework for evaluating the regulatory, ecological, and hydrogeomorphic components using 15 years of fish spawning habitat construction in the St. Clair‐Detroit River System. The process began by identifying regulatory requirements at a coarse resolution to quickly focus on locations where ecological potential and hydrogeomorphic constraints could be assessed at finer resolutions. Next, ecological potential was assessed using a lithophilic fish spawning habitat suitability index. The suitability index identified five sites for habitat construction and lake sturgeon spawning was documented at each site following construction. However, qualitative monitoring showed fine sediments accumulated at older sites. Thus, geomorphic assessments were incorporated to identify sediment sources and model flow within targeted areas. Since geomorphic assessments required the finest resolution and had the most uncertainty, they were conducted after broad‐scale regulatory considerations and ecological assessments narrowed focus to a few candidate sites. The order of operations identified in this case study evolved from the iterative approach of the restoration team, but in retrospect, it helped develop a framework that directed project development resources to aspects with more uncertainty, where learning is most critical.